Motivation Labor Women In Increasing Family Income Through pineapple farming (Ananas comusus L. Merr) in the Lubuk Karet Village Betung District Banyuasin Regency - Darayani, Nina; Sobri, Khaidir; Kurniawan, Rahmat (Muhammadiyah University of Palembang, 2015)
Motivation Labor Women In Increasing Family Income Through pineapple farming (Ananas comusus L. Merr) in the Lubuk Karet Village Betung District Banyuasin Regency. The purpose of this study was to determine the motivation of women workers, to determine the outpouring of women workers, to determine the contribution of pineapple farm income. This research was condusted in the Lubuk Karet Village Betung District Banyuasin Regency of July until the month of Agustus 2015. The method used was a survey, While the sampling method used is the method by farmers census respondents as many as 19 people. Data collection method used observation and interviews directly to farmers. To answer the first problem formulation using qualitative descriptive analysis with a qualitative approach. The survey results revealed that the motivation of women farmers to come to work on a pineapple farm belonging to the category with a score of real low and the percentage obtained for 2021 (70.91%). With each variable spare time with thepercentage of 84.10%, followed by the variable no other job opportunities in accordance skill of 67.68% and a variable meet the economic needs of 60.94 %. The outpouring of female workers on a pineapple farm on average 36.00 HKSP. Pineapple farm income contributes to the family income average of 71.93 %.